Capacity and Error Rate Analysis of MIMO Satellite Communication Systems in Fading Scenarios - Ramoni Adeogun (International Journal of Electrical and Computer Engineering (IJECE), 2014)
In this paper, we investigated the capacity and bit error rate (BER) performance of Multiple Input Multiple Output (MIMO) satellite systems with single and multiple dual polarized satellites in geostationary orbit and a mobile ground receiving station with multiple antennas. We evaluated the effects of both system parameters such as number of satellites, number of receive antennas, and SNR and environmental factors including atmospheric signal attenuations and signal phase disturbances on the overall system performance using both analytical and spatial models for MIMO satellite systems.DOI:http://dx.doi.org/10.11591/ijece.v4i4.5349